Marketing research : applied insight - Malhotra, Naresh K. (Pearson, 2020)
"Working as a marketing researcher remains an intellectually stimulating, creative and rewarding career. Marketing research is a huge and growing industry at the forefront of innovation in many sectors of the economy. However, few industries can have been presented with as many challenges and opportunities as those faced by marketing research due to the growing amounts of data generated by modern technology. Founded upon the enormously successful US edition, and building upon the previous five European editions, the sixth edition of this book seeks to maintain its position as the leading marketing research text, focused on the key challenges facing marketing research in a European context. As with previous editions, this aims to be comprehensive, authoritative and applied. As a result, the book covers all the topics in previous editions while including updates that reflect the changes and challenges that have impacted the marketing research sector since the fifth edition was published. This includes the ever shifting impact of new technologies, the growth of 'insight' and the shifting role of research ethics, for example, through considering the impact of GDPR. This edition has been significantly updated, with new content, updated cases studies and a major focus on the issues and methods generated by new technologies".